The Zodiac of Paris : How an Improbable Controversy over an Ancient Egyptian Artifact Provoked a Modern Debate between Religion and Science - Buchwald, Jed Z.; Josefowicz, Diane Greco (Book collections on Project MUSE., 2010)
The Dendera zodiac--an ancient bas-relief temple ceiling adorned with mysterious symbols of the stars and planets--was first discovered by the French during Napoleon's campaign in Egypt, and quickly provoked a controversy between scientists and theologians. Brought to Paris in 1821 and ultimately installed in the Louvre, where it can still be seen today, the zodiac appeared to depict the nighttime sky from a time predating the Biblical creation, and therefore cast doubt on religious truth. The Zodiac of Paris tells the story of this incredible archeological find and its unlikely role in the fierce disputes over science and faith in Napoleonic and Restoration France --Publisher's description.